2019
DOI: 10.1037/cpp0000268
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability, and preliminary effectiveness of an adaptive text messaging intervention for adolescent weight control in primary care.

Abstract: Behavioral interventions for adolescent weight control are often difficult to access because they are rarely provided in primary health care. This study was designed to assess the feasibility, acceptability, and preliminary effectiveness of a motivational interviewing plus adaptive text messaging intervention for adolescent weight control delivered in primary care. Methods: Forty-seven overweight adolescents (aged 13-18 years) participated in a single, hour-long, in-person motivational interviewing session in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(86 citation statements)
references
References 27 publications
(35 reference statements)
3
80
0
Order By: Relevance
“…Study interventions varied immensely in treatment modality and content. The interventions included mobile phone app interventions [ 42 , 48 , 49 ], text-based interventions [ 19 , 60 , 61 ], home-delivered interventions with technology adjunct components [ 34 , 63 ], group sessions or interactive classes with phone calls [ 53 , 58 ], group-based exergames [ 78 ], exergaming in addition to family-based behavioral treatment [ 82 ], and active video games as replacements for non-active video games [ 75 ], among others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study interventions varied immensely in treatment modality and content. The interventions included mobile phone app interventions [ 42 , 48 , 49 ], text-based interventions [ 19 , 60 , 61 ], home-delivered interventions with technology adjunct components [ 34 , 63 ], group sessions or interactive classes with phone calls [ 53 , 58 ], group-based exergames [ 78 ], exergaming in addition to family-based behavioral treatment [ 82 ], and active video games as replacements for non-active video games [ 75 ], among others.…”
Section: Resultsmentioning
confidence: 99%
“…Two of these 27 studies (8%) reported significant improvement in measures of adiposity (e.g., percent body fat, BMIz) in both the intervention and active comparator groups at post-intervention, with one intervention delivered solely through technology [ 41 ] and the other using technology adjunctively [ 81 ]. Despite finding no differences between conditions, five studies reported significant improvements in measures of adiposity among those in the intervention groups [ 19 , 51 , 60 , 66 , 70 ], which all had active comparators. Two treatment studies that reported overall null findings did report significant effects for the intervention in subgroups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 215 full-text articles were assessed for edibility, and 201 were excluded with reasons outlined in Figure 1 and Multimedia Appendix 4. Eight unique studies [35][36][37][38][39][40][41][42] from 13 publications were included in this review [24,[35][36][37][38][39][40][41][43][44][45][46][47].…”
Section: Study Selectionmentioning
confidence: 99%
“…All studies measuring BMI (kg/m 2 ) measured height and weight in person by trained personnel using standardized procedures and calibrated equipment (Table 2). The 5 studies calculating BMI z-score specified the country of origin for the age-and sex-specific reference values [37,[39][40][41][42]. Of the 8 studies, 7 demonstrated reductions in BMI or BMI z-score in the intervention group compared with the control at the end of the final follow-up (Table 3).…”
Section: Body Mass Indexmentioning
confidence: 99%